Small tourism business research change and evolution - Morrison, A.; Carlsen, Jack; Weber, Paul (John Wiley & Sons, 2010)
The paper critically reflects on key knowledge contributions that coalesce to inform contemporary understanding of the phenomenon of small tourism business. The purpose is to scrutinise change and evolution in perspectives and how these impact on what knowledge is disclosed and what is not. Conventionally accepted wisdom is challenged, indoctrinated presuppositions are questioned, and research methodological advancements are offered. This is achieved through a comprehensive review and critical-reflective analysis of key academic contributions spanning a period of approximately 35 years. The value is to stimulate criticality relative to what constitutes ‘truth’ within the given context and to inspire fresh research perspectives. Conclusions are drawn regarding future research directions. Furthermore, informed by thorough analysis of the content of the paper, five guiding research principles provide an appropriate conclusion.